2019
DOI: 10.1158/1538-7445.am2019-ct213
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT213: ORIENT-16: Sintilimab plus XELOX vs placebo plus XELOX as 1st line treatment for unresectable advanced gastric and GEJ adenocarcinoma

Abstract: Background: Gastric cancer is one of the most common malignant tumors worldwide, and the 2nd most common in China. The development of new agents for the treatment of advanced gastric cancer is stagnant. Immunotherapy which inhibits the programmed death 1 (PD-1)/ programmed death ligand 1 (PD-L1) interaction is becoming a new option for treatment of late-stage gastric cancer (GC). Several trials suggest patients with PD-L1 positive expression (Combined Positive Score: CPS ≥ 1) population, especially CPS ≥ 10 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…CheckMate 649 is the most robust dataset to date to report PD-L1 CPS ≥ 5 prevalence using an analytically validated assay (28-8 pharmDx) in gastric, GEJ or oesophageal adenocarcinoma. The phase 3 ORIENT-16 trial in China reported a similar PD-L1 CPS ≥ 5 prevalence of approximately 60% using the 22C3 PharmDx assay 17 , 18 . In CheckMate 649, the magnitude of survival benefit continued to be enriched with nivolumab plus chemotherapy versus chemotherapy in patients with higher PD-L1 CPS, consistent with results at 12-month follow-up 5 .…”
Section: Discussionmentioning
confidence: 95%
“…CheckMate 649 is the most robust dataset to date to report PD-L1 CPS ≥ 5 prevalence using an analytically validated assay (28-8 pharmDx) in gastric, GEJ or oesophageal adenocarcinoma. The phase 3 ORIENT-16 trial in China reported a similar PD-L1 CPS ≥ 5 prevalence of approximately 60% using the 22C3 PharmDx assay 17 , 18 . In CheckMate 649, the magnitude of survival benefit continued to be enriched with nivolumab plus chemotherapy versus chemotherapy in patients with higher PD-L1 CPS, consistent with results at 12-month follow-up 5 .…”
Section: Discussionmentioning
confidence: 95%
“… 21 In vitro, compared to nivolumab or pembrolizumab, sintilimab has a higher binding affinity and is able to bind with more PD-1 molecules on CD3 + T cells, and has better T cell activating characteristics. 21 In a phase 1b study (NCT03745170), sintilimab combined with oxaliplatin/capecitabine has shown promising efficacy in gastric cancer with an ORR of 85% 22 which warranted a phase 3 ORIENT-16 study (NCT03745170) to further investigate the therapeutic potential of sintilimab in combination with chemotherapy in patients with advanced G/GEJ cancers. 23 The interim results from ORIENT-16 study were orally presented on 2021 ESMO, in which sintilimab was demonstrated to be the first PD-1 inhibitor to show superior OS and PFS with an acceptable safety profile, in combination with chemo, in Chinese patients with G/GEJ cancer regardless of PD-L1 expression status.…”
Section: Introductionmentioning
confidence: 99%
“…The ATTRACTION-4 study in Asian population showed a comparable safety profile in the nivolumab-chemotherapy group compared with that in the placebo-chemotherapy group, with neutropenia being the most common grade 3 to 4 adverse event ( 13 ). The ORIENT-16 study in the Chinese population found that the incidence rate of grade ≥3 TRAEs in the sintilimab-chemotherapy group was comparable with that in the chemotherapy group (59.8% vs. 52.5%, p = 0.063) ( 51 ). A meta-analysis comparing the safety of different combinations of immunotherapy and chemotherapy regimens showed that the incidence rate of TRAE ≥3 grade was similar between PD-1 inhibitor with oxaliplatin-based chemotherapy and that with cisplatin-based chemotherapy (RR = 0.86, 95% CI, 0.66–1.12), whereas, among patients with oxaliplatin-based chemotherapy, the incidence rate of TRAE ≥3 times was comparable between those combining nivolumab and those combining sintilimab ( 52 ).…”
Section: Discussionmentioning
confidence: 99%